Skrining Frambusia Pada Anak Di Bawah 15 Tahun Di Perbatasan Jayapura Dengan Metode Rapid Diagnostic Test - Sumolang, Inneke Viviane; Sidabutar, Astrina Rosaria Indah; Rusman, Nuraliah (Pakis Journal Institute, 2025)
Yaws is a tropical skin disease that can cause serious complications if left untreated. The border area between Indonesia and Papua New Guinea, especially in the Muara Tami district, Jayapura, Papua, is one of the endemic areas for yaws with limited access to health services. This community service activity aims to conduct early detection of yaws in children in the area using the rapid diagnostic test (RDT) method. The activity was carried out at the Moso Village Health Center, Muara Tami district. Samples were taken purposively, with the inclusion criteria being children under 15 years of age who live in Moso village. Yaws examination using RDT was carried out on 17 children, followed by treatment for those who tested positive. There were 4 positive cases of yaws or 23.52% detected from 17 participants who had received RDT examination. In addition, the achievement of this activity has educated parents of yaws screening participants about the symptoms and prevention of yaws so that it can increase the capacity of the local health system and public awareness in efforts to eliminate yaws. The prevalence of yaws in the border area is still quite high. The use of RDT has proven effective for the detection and monitoring of yaws, although there are still challenges in ensuring compliance and completion of treatment. Long-term monitoring is needed to evaluate the effectiveness of the intervention comprehensively.